THE EFFECT OF SMALL AMOUNTS OF H2O ON CRYSTALLISATION OF MID-OCEAN RIDGE AND BACKARC BASIN MAGMAS - Danyushevsky L.V. (My University, 2001)
The main effects of H2O on crystallisation of basaltic liquids are to decrease melt liquidus temperature and to suppress plagioclase crystallisation relative to olivine and clinopyroxene. Although MORB magmas contain small amounts of H2O, for petrological purposes these magmas have been considered to be anhydrous. In this paper, the effect of small amounts of H2O on fractionation paths of MORB and BABB magmas is investigated by comparing the compositions of MORB and BABB glasses with the results of anhydrous experiments on MORB-like compositions. This effect is shown to be large enough that it should be considered when using glass compositions for the purposes of understanding MORB petrogenesis. The effect of H2O is strongly non-linear. The decrease of melt liquidus temperature can be obtained from the effect of H2O on the olivine crystallisation: Olivine Liquidus Depression . The suppression of plagioclase crystallisation relative to olivine is: Plagioclase Liquidus Depression Relative to Olivine . The presence of H2O produces the most pronounced effect on concentrations of Al2O3, FeO∗ and TiO2 in cogenetic suites of MORB and BABB. It also results in a smaller degree of fractionation for a given cooling interval. The computer program petrolog that performs modelling of magma fractionation at variable H2O contents is available from the author.